Feelings of Homesickness. Writing Practices of Young Bourgeois Men in the Nineteenth Century and the Role of Gender and Emotions in Youth Diary-Writing Cultures - Wehren, Sylvia (Acta Poloniae Historica, 2025)
This article explores the diaries of young bourgeois men from the nineteenth century. It focuses on homesickness as an emotional experience shaped by gender and social expectations. Diaries have long been linked to femininity, but many boys and young men also kept diaries, especially when leaving home for school or university. The selected diaries of four boys reveal close ties to family, reflections on masculinity, and emotional struggles related to separation. Their writings often depict homesickness as a test of character, framing their emotions within cultural ideals of male strength, courage, and religious devotion. The diaries also functioned as tools for self-regulation, memory, and emotional agency, allowing the authors to manage feelings through writing. The study shows how diary-keeping shaped emotional and gender identity. It proves that nineteenth-century masculinity was not only about duty and purpose, but also deeply intertwined with love, longing and personal transformation.